Design and verification of energy balance actuation system for fishbone morphing wings - Yan ZHAO; Chen WANG; Ziyi HE; Jixu CAI; Yu ZHANG; Xing SHEN; Jiaying ZHANG (工程科学学报)
Morphing wings can improve the aerodynamic performance of aircraft and expand their flight envelope. Elastic deformation of the morphing structure can enable continuous and smooth shape changes of the morphing aircraft, which is important in morphing technologies. However, airframe structures need to resist aerodynamic loads, and elastic deformation consumes a significant amount of energy during the morphing process, which increases the weight and size of the actuation system, undermining the morphing benefits. To address this problem, an actuation system based on the energy-balancing principle is proposed to reduce the energy requirement of the morphing wing, thereby reducing its weight and size. The energy-balancing principle is achieved using the elastic strain energy of structural deformation during morphing. Because the structural deformation corresponding to morphing is elastic, the strain energy can be recycled, which reduces energy requirements. The recovery and utilization of the elastic strain energy can be achieved by integrating the energy storage elements in the actuation mechanism. Theoretically, if friction is not considered, the actuation energy required to deform the structure can be provided by the energy storage elements without the need for any external energy. This will result in the overall system achieving the energy-balancing state and significantly reduce the energy consumption. In addition, from the perspective of stiffness, the energy-balancing state suggests a quasi-zero overall stiffness of the actuation system, and a negative-stiffness mechanism associated with the structural stiffness is required to create a quasi-zero overall stiffness. In the current study, a negative-stiffness mechanism based on the spiral pulley mechanism was first designed. The stiffness provided by the spiral pulley mechanism can balance the structural stiffness required for structural deformation, which creates a quasi-zero-stiffness system and reduces the actuation force requirement because the overall stiffness of the system is close to zero. A prestretched spring was used as an energy storage element, and a kinematic model was established to analyze the motion process. The moment output and magnitude of the negative stiffness generated during the motion process were derived. The stiffness of the deformed structure was measured, and the negative-stiffness mechanism was optimized using a genetic algorithm. The optimization results show that the negative-stiffness of the system can significantly reduce the energy requirement. However, the stiffness of the morphing wing structure varies from the design point because of manufacturing, assembly, and other factors. Considering the disturbances and uncertainties of the system, a stiffness-tuning mechanism was introduced to enhance the adaptability of the negative-stiffness mechanism. By changing the position of the connection point of the spring, the negative and overall stiffness can be adjusted. Theoretical analysis shows that the range of the overall stiffness expanded, allowing the system to better satisfy energy-balancing requirements under varying structural stiffnesses. Finally, the actuation system is integrated into a fishbone morphing wing, and the experimental platform is established. Actuation experiments were conducted and the currents of the servo actuator were measured using the current sensor. The experimental results show that the energy-balancing system can reduce energy consumption by 44.54%, which indicates that the energy-balancing method has the potential to significantly reduce energy consumption. In addition, it was verified that the stiffness-tuning mechanism can adjust the structural stiffness by tuning the connection point position, which can improve the effectiveness of the energy-balancing system.